2009
DOI: 10.1007/s00586-009-1065-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thoracic pedicle screw placement in adolescent idiopathic scoliosis

Abstract: Pedicle screw fixation is a challenging procedure in thoracic spine, as inadvertently misplaced screws have high risk of complications. The accuracy of pedicle screws is typically defined as the screws axis being fully contained within the cortices of the pedicle. One hundred and eighty-five thoracic pedicle screws in 19 patients that were drawn from a total of 1.797 screws in 148 scoliosis patients being suspicious of medial and lateral malpositioning were investigated, retrospectively. Screw containment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
61
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 19 publications
0
61
1
3
Order By: Relevance
“…Considering the complexity of pedicle anatomy, pedicle screw insertion could be mentally and technically demanding [26,27]. The priority is to make sure that each screw is contained solely in the desired pedicle and its alignment with its neighbors often comes after this priority [27][28][29]. Even with computer-assisted image-guided techniques, there is considerable variation in the placement of each pedicle screw with respect to its neighbors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the complexity of pedicle anatomy, pedicle screw insertion could be mentally and technically demanding [26,27]. The priority is to make sure that each screw is contained solely in the desired pedicle and its alignment with its neighbors often comes after this priority [27][28][29]. Even with computer-assisted image-guided techniques, there is considerable variation in the placement of each pedicle screw with respect to its neighbors.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in screw insertion orientation is also significant, sometimes with pedicle violation (medial, inferior, superior, and anterolateral vertebral body) [27]. Variation of coronal plane screw position greater than 2 mm was reported (distance between medial pedicle wall and medial margin of the pedicle screw and between lateral margin of the pedicle screw and lateral vertebral corpus) [29]. The final positions of all screw head slots are therefore unlikely to be perfectly smoothly aligned.…”
Section: Discussionmentioning
confidence: 99%
“…The overall rate of misplacement reported in this study was 17%. Five of the studies dealing with assessment of pedicular screw placement in scoliosis showed a misplacement rate of 5.7, 50.7, 25, 29.1, and 18.5% [1,3,9,20,22].…”
Section: Discussionmentioning
confidence: 99%
“…21,25,32 Pedicle screw placement, however, can be challenging, particularly in the thoracic spine. 17,19,21,37 In this region, the pedicles are typically smaller and have more complex morphologies, thus increasing the risk of malpositioned screws.…”
Section: Discussionmentioning
confidence: 99%